An ecological approach to caregiver burnout: interplay of self-stigma, family resilience, and caregiver needs among mothers of children with special needs - Tang, Catherine So-Kum; Yu, Isaac Chun-Yeung; Ng, Kai-hang; Kwok, Helen Sin-Hang (Frontiers in Psychology, 2025)
IntroductionUsing an ecological framework, this study investigated how individual perceptions (self-stigma), family dynamics (family resilience), and external support systems (caregiver needs) interacted with each other to impact caregiver burnout among mothers of children with special needs (SN) in Hong Kong.MethodsA total of 250 Chinese mothers of children with SN in Hong Kong completed an online survey.ResultsPearson correlation analyses indicated that high levels of caregiver burnout were significantly related to high levels of self-stigma, high levels of unmet caregiver needs, and low levels of family resilience. Multiple regression analysis revealed significant main effects and a 3-way interaction effect of these three factors on caregiver burnout. The significant 3-way (self-stigma X family resilience X caregiver needs) interaction effect showed that in conditions of low self-stigma, the highest level of caregiver burnout was found among mothers with low family resilience and high caregiver needs. Conversely, in conditions of high self-stigma, the highest level of burnout was observed among mothers with high family resilience and high caregiver needs.DiscussionThe findings of this study underscore the necessity of a holistic and culturally sensitive approach to effectively reducing the caregiving burden among Chinese mothers of children with SN. Addressing caregiver burnout in these mothers requires simultaneous efforts to reduce self-stigma through psychological support, educate families to manage expectations and alleviate pressure, and enhance society resources to meet caregiver needs.